Three new species of the genus Caccothryptus Sharp, 1902 from Asia (Coleoptera: Limnichidae) - Hernando, Carles; Ribera, Ignacio (Zootaxa, 2017)
Caccothryptus Sharp, 1902 is a genus of Limnichidae with a mainly Oriental distribution, with only some species at the fringes of the Palaearctic (Hernando & Ribera 2014, 2016). The genus was recently revised by Hernando & Ribera (2014), which described 14 new species and divided the by then 20 species in five species groups, the compactus, rouyeri, testudo, jaechi and zetteli groups. Subsequently, Yoshitomi (2015) described four additional species in the C. testudo group, rising the total number of species to 24. In this paper we describe three additional species in the testudo and compactus groups, among them the so far westernmost species of the genus, from Uttarakhand (India).